Case report: Sarcomatoid urothelial carcinoma of the renal pelvis masquerading as a renal abscess - Chu, Yaru; Ning, Hao; Yin, Ke; Chen, Tong; Wu, Haihu; Wang, Delin; Liu, Feifan; Zhao, Zhenlin; Lv, Jiaju (Frontiers in Oncology, 2023)
Sarcomatoid urothelial carcinoma (SUC), a rare tumor of the urinary tract epithelium, exhibits a high degree of malignancy and therefore a poor prognosis. Due to the absence of specific clinical presentations and imaging findings, SUC of the renal pelvis masquerades as a renal abscess is frequently under-recognized or misdiagnosed as benign inflammatory disease, resulting in delayed or erroneous treatment. Here, we report a patient with SUC of the renal pelvis who presented with a renal abscess. Repeated anti-inflammatory treatment was ineffective. Unexpectedly, cancerous cells were detected in subsequent exfoliative cytology of nephrostomy drainage fluid. In accordance with this, radical surgery and postoperative chemotherapy were conducted. Fortunately, neither recurrence nor metastasis occurred during a one-year follow-up.